If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 4 = 0.5(2x + -7) Reorder the terms: 4 + x = 0.5(2x + -7) Reorder the terms: 4 + x = 0.5(-7 + 2x) 4 + x = (-7 * 0.5 + 2x * 0.5) 4 + x = (-3.5 + 1x) Solving 4 + x = -3.5 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 4 + x + -1x = -3.5 + 1x + -1x Combine like terms: x + -1x = 0 4 + 0 = -3.5 + 1x + -1x 4 = -3.5 + 1x + -1x Combine like terms: 1x + -1x = 0 4 = -3.5 + 0 4 = -3.5 Add '-4' to each side of the equation. 4 + -4 = -3.5 + -4 Combine like terms: 4 + -4 = 0 0 = -3.5 + -4 Combine like terms: -3.5 + -4 = -7.5 0 = -7.5 Simplifying 0 = -7.5 Combine like terms: 0 + 7.5 = 7.5 7.5 = -7.5 + 7.5 Combine like terms: -7.5 + 7.5 = 0.0 7.5 = 0.0 The solution to this equation could not be determined.
| 5q+p=q-3 | | 3(7x+9)=48 | | x^2+y^2=1600 | | 7*[3(3)-2]+5=6*[2(3)-1]+24 | | 2cos^2-5cos-3=0 | | 6=-3+33 | | k-15=-30 | | tn=3n-1 | | 9+4x=23 | | 4X+11=2X^2+13X+6 | | -7(-6x+2)=48 | | 5(x+11)=5(12-x) | | 4x+9=-31-4x | | e-6=7 | | tn=tn-1-4 | | 4(-7+2x)=-28 | | 3(3-y)1=31 | | -4x^3+4x^2+35x=0 | | 2-a=3 | | 4x-23x+18x-278=34 | | x^2-1040x=0 | | 7[3(3)-2]+5=6[2(3)-1]+24 | | 44x-23+18x-278=34 | | m+8=-10 | | X-(-x-2)=-8 | | 44x-23+18x-278=345 | | 3x-5=-12x-59 | | tn=4n+3 | | 11x-6=7x+7 | | (3x+6)(x+7)=0 | | 3x+25-27x=12 | | 9v^2+37v+4=0 |